Effect of process parameters on machining behaviour using S/N ratio and ANOVA analysis. (2023) - Balaji, S.; Sivakandhan, C.; Maniarasan, P.; Deepak, D.; Senthamarai, K.; Alagarsamy, S.V.
Abstract: Inconel 725 super alloy is a significant and often used material for many technical applications such as oil and gas industries, aerospace, nuclear and marine areas owing to its exceptional physical and mechanical properties. The major drawback of utilizing this alloy is challenging it is to machine using traditional machining techniques. Production sectors often aim to produce goods with excellent surface finishes and high production rates at reasonable prices. Hence, in the current study deals with the effect of electric discharge machining (EDM) parameters viz. pulse-on time (Ton ), pulse-off time (Toff ) and discharge current (Ip ) on metal removal rate (MRR) and surface roughness (Ra) of Inconel 725 alloy. According to the Taguchi's L9 orthogonal design the EDM studies were performed. The optimal condition of EDM parameters was obtained by signal to noise (S/N) ratio analysis with an aim was to minimize the Ra and maximize the MRR. S/N ratio results obtained that the higher MRR produced at Ton of 45 µs, Toff of 60 µs and Ip of 10 A. Similarly, the lower Ra produced at Ton of 15 µs, Toff of 40 µs and Ip of 5 A. ANOVA results reveals that discharge current (Ip ) has the most noteworthy factor for MRR and Ra followed by pulse-on time (Ton ).